Development of a microarray-based assay for efficient testing of new HSP70/DnaK inhibitors. Issue 24 (15th December 2017) - Mohammadi-Ostad-Kalayeh, Sona; Hrupins, Vjaceslavs; Helmsen, Sabine; Ahlbrecht, Christin; Stahl, Frank; Scheper, Thomas; Preller, Matthias; Surup, Frank; Stadler, Marc; Kirschning, Andreas; Zeilinger, Carsten
Graphical abstract: Abstract: A facile method for testing ATP binding in a highly miniaturized microarray environment using human HSP70 and DnaK from Mycobacterium tuberculosis as biological targets is reported. Supported by molecular modelling studies we demonstrate that the position of the fluorescence label on ATP has a strong influence on the binding to human HSP70. Importantly, the label has to be positioned on the adenine ring and not to the terminal phosphate group. Unlabelled ATP displaced bound Cy5-ATP from HSP70 in the micromolar range. The affinity of a well-known HSP70 inhibitor VER155008 for the ATP binding site in HSP70 was determined, with a EC50 in the micromolar range, whereas reblastin, a HSP90-inhibitor, did not compete for ATP in the presence of HSP70. The applicability of the method was demonstrated by screening a small compound library of natural products. This unraveled that terphenyls rickenyl A and D, recently isolated from cultures of the fungus Hypoxylon rickii, are inhibitors of HSP70. They compete with ATP for the chaperone in the range of 29 µM (Rickenyl D) and 49 µM (Rickenyl A). Furthermore, the microarray-based test system enabled protein–protein interaction analysis using full-length HSP70 and HSP90 proteins. The labelled full-length human HSP90 binds with a half-maximal affinity of 5.5 µg/ml (∼40 µM) to HSP70. The data also demonstrate that the microarray test has potency for many applications from inhibitor screening to target-oriented interaction studies.